Delivery of doxorubicin by dual responsive carboxymethyl chitosan based nanogel and in vitro performance. (June 2022) - Yang, Lianlian; Ling, Junhong; Wang, Nan; Jiang, Yongjun; Lu, Yuqing; Yang, Li-Ye; Ouyang, Xiao–kun
Abstract: Here, glycidyl methacrylate (GMA) was used for modification of carboxymethyl chitosan (CMCS). The double bond on the side group of CMCS was polymerized and cross-linked with N-N′-bis(acryloyl) cysteamine (BAC), containing a disulfide bond, and modified with folic acid (FA) to obtain nanogels for the targeted delivery of doxorubicin (DOX). Effectiveness of DOX delivery and release were subsequently investigated. The drug encapsulation efficiency (EE) and loading capacity (LC) of DOX were 94.77 ± 0.83% and 15.6 ± 0.12%, respectively. The particle size of the GCMCS-FA-DOX nanoparticles loaded with DOX was 220.4 ± 38.4 nm. The experimental results showed that GCMCS-FA-DOX had a high glutathione and pH response performance. GCMCS-FA-DOX showed an improved inhibitory effect on tumor cell proliferation compared to free DOX. GCMCS-FA-DOX significantly improved the efficiency of drug uptake by cells, and the cytotoxicity of GCMCS-FA-DOX in HCT-116 tumor cells was higher than that in HepG-2 tumor cells. Graphical Abstract: ga1